2014
DOI: 10.1371/journal.pone.0092701
|View full text |Cite|
|
Sign up to set email alerts
|

Lesions of the Lateral Habenula Increase Voluntary Ethanol Consumption and Operant Self-Administration, Block Yohimbine-Induced Reinstatement of Ethanol Seeking, and Attenuate Ethanol-Induced Conditioned Taste Aversion

Abstract: The lateral habenula (LHb) plays an important role in learning driven by negative outcomes. Many drugs of abuse, including ethanol, have dose-dependent aversive effects that act to limit intake of the drug. However, the role of the LHb in regulating ethanol intake is unknown. In the present study, we compared voluntary ethanol consumption and self-administration, yohimbine-induced reinstatement of ethanol seeking, and ethanol-induced conditioned taste aversion in rats with sham or LHb lesions. In rats given ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
52
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 62 publications
(67 citation statements)
references
References 41 publications
(57 reference statements)
12
52
2
1
Order By: Relevance
“…Interestingly, a previous study found that lesions of the LHb increase voluntary ethanol drinking and operant-self administration in rats (Haack et al, 2014), in contrast to the reduced drinking after DBS observed in our current study. The mechanisms underlying the disparity are unclear.…”
Section: Discussioncontrasting
confidence: 99%
“…Interestingly, a previous study found that lesions of the LHb increase voluntary ethanol drinking and operant-self administration in rats (Haack et al, 2014), in contrast to the reduced drinking after DBS observed in our current study. The mechanisms underlying the disparity are unclear.…”
Section: Discussioncontrasting
confidence: 99%
“…For instance, studies found that rats drink more alcohol if the LHb was lesioned before the start of drinking (Haack et al, 2014; Tandon et al, 2017), indicating that the LHb plays a brake-like role during the acquisition phase. Conversely, we found that temporal inhibition of the LHb by DNQX or chemogenetic tool reduced drinking in rats that have been drinking ethanol for two months, when the animals may have already become ethanol dependent (Li et al, 2011b).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, direct excitation of VTA-GABA neurons disrupts reward-related behaviors (van Zessen et al, 2012), and stimulation of VTA-GABA neurons or inhibition of VTA-dopamine neurons promotes aversion (Tan et al, 2012). Interestingly, Taha and colleagues showed that lesions of the LHb increases ethanol consumption (Haack et al, 2014); which may be due to the reduction of RMTg activity, since RMTg receives a major excitatory input from LHb.…”
Section: Discussionmentioning
confidence: 99%